High Performance Thermoplastic Resins and Their Composites - Béland, Sylvie (Noyes Data Corporation, 2011)
Recent developments in high performance thermoplastic resins and their composites are described in this book, and the benefits and limitations of these emerging materials are assessed for aerospace and other applications.